Design research investigation for successful creative solutions - Leonard, Neil.; Ambrose, Gavin (Lausanne, Switzerland AVA Academia, 2012)
Design research will guide the reader through the early stages of a design project, identifying appropriate research techniques and enabling innovative solutions to be found.
Keywords: Graphic arts; Graphic design; Commercial art